CAUSALITY ANALYSIS OF RICE PRICES WITH INFLATION RATE IN INDONESIA - Anggityas Werdining Pangesti; Darsono Darsono; Ernoiz Antriyandarti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Indonesia is one of the countries with the largest rice consumption in the world. The strategic value of rice places it as a commodity contributing to inflation. This study aims to investigate the causal relationship between rice prices and the inflation rate in Indonesia and to analyze the role of rice prices in the inflation rate in Indonesia. The rice price and inflation rate data used are secondary data with monthly periods obtained from the Indonesian Central Bureau of Statistics, Bulog (The National Logistics Agency), Ministry of Agriculture, Ministry of Trade, FAO and United States Department of Agriculture, and the United States Census Bureau. The analysis was carried out using Granger Causality and Vector Error Correction Model (VECM) utilized by the E-Views application. The Granger Causality test results show a causality relationship between rice prices and the inflation rate in Indonesia with a bi-directional causality pattern. We also found a long-run relationship. Impulse Response Function shows that shock in the rice prices will affect inflation throughout the sixth month until it converges and is stable. In line with the results of the Impulse Response Function, analysis of Variance Decomposition shows that changes in rice prices play a role in explaining the difference in the inflation rate of 2,77%.